Educating for resilience: parent and teacher perceptions of children's emotional needs in response to climate change. Issue 5 (27th May 2021) - Baker, Cambry; Clayton, Susan; Bragg, Eshana
Abstract: Children are worried about climate change. Environmental education aims to increase knowledge and pro-environmental behavior but typically gives little attention to meeting children's emotional needs. This is particularly important as direct and indirect impacts of climate change, including the Australian bushfires in 2019–20, become more salient. This study explored caretaker perceptions of children's climate change emotions, and the needs and challenges around supporting children, through an online survey of Australian parents and teachers ( n = 141). Parents and teachers similarly reported that children experience anxiety and express interest in talking about climate change. They described challenges that inhibit their ability to talk to the children, whilst also identifying positive experiences of doing so. We conclude that parents and teachers would benefit from resources to help them support their children's environmental learning in a way that fosters emotional wellbeing and promotes hopefulness. We suggest principles that acknowledge feelings, emphasize solutions, and encourage action.